Analysis of structural, optical and electrical properties of nano-particulate indium doped zinc oxide thin films. (18th October 2019) - Sahoo, Bijayalaxmi; Behera, Debadhyan; Pradhan, Siddhartha K; Mishra, Dilip Kumar; Sahoo, Susanta Kumar; Nayak, Rati Ranjan; Sekhar, Kanaparedu P C
Abstract: Indium doped ZnO thin films were deposited on glass substrates by spray pyrolysis technique with variation of indium concentration within a range of 0–5 at% and annealed at 500 °C for 2 h in presence of air. Preferentially oriented ZnO films along (002) plane has been obtained at 1 at% indium doping concentration. The particle size is found to be decreased with increase in dopant concentration as a result of lowering of cohesion in ZnO. The 5 at% indium doped ZnO film has a better compact morphology due to better grain boundary interactions for which it shows highest hall mobility in comparison to the all concentration of indium doped samples. The marginal band gap shift with In doping is attributed to Burstein-Moss shift. Highest thermal activation energy of 0.78 eV has been observed in case of 3 at% indium doping. The origin of the observed visible emission peaks at 450 nm, 468 nm, 480 nm, 490 nm and 670 nm are ascribed to various defects present within the bandgap.